Financial and non-financial aspects of entrepreneurship: The Polish perspective - Karolina Palimąka (Financial Internet Quarterly, 2021)
The phenomenon of entrepreneurship has various perspectives - economic, financial, social, and psychological. The aim of this paper is to present entrepreneurship from a perspective merging both financial and non-financial aspects of this phenomenon. The article presents two (complementary) aspects related to the phenomenon of entrepreneurship. One of the aspects described by author is the availability of financing for businesses in Poland (showing the issue in response to the most important obstacle to running a business), the other is shaping entrepre- neurial attitudes. The section on sources of financing give an answer to the question of whether (and if so - to what extent) the problem of access to financing is a real barrier to starting a business in Poland. Presenting the perspective of students gives a new view on the subject and enables us to recognize factors that determine the decision to start a business among young people, knowledge of which may contribute to a change in attitudes towards setting up a business in Poland. Among the conclusions, the author mentions, inter alia, the need to strengthen entrepreneurial attitudes among students, especially due to the growing number of companies operating in Poland for reasons of positive motivation (such as improvement of the standard of living or independence). Moreover, the conducted analyses lead to the conclusion that new companies are financed primarily from their own resources, which discourages many from starting their own business.
Keywords: L26; D25; J23; J24; 330; Poland; financing a business; entrepreneurship intention; entrepreneur attitude; students; own business